Reform Rabbi Herbert Weiner’s writings on religion in Israel in the 1950s and 1960s - Kaplan, Dana Evan (Journal of Jewish studies, 2022)
As an important yet virtually ignored American Jewish thinker, Rabbi Herbert Weiner was the first post-World War II Reform theologian to embrace Jewish mysticism. Weiner’s writings were deeply influenced by Zionist theoretical thought as well as his extensive and frequent sabbaticals in British Mandatory Palestine and later the State of Israel. Fascinated by both Kabbalah and Hasidism, Weiner was particularly influenced by Rabbi Abraham Isaac Kook. This article looks at the impact of Weiner’s temporary appointment as administrator of the Hebrew Union College campus in Jerusalem in the early 1960s and the difficulties that this created for him in his relationships with Israeli Orthodox mystics, including Rabbi Zvi Yehudah Kook. The article makes a contribution to the study of the intellectual relationships between American Reform and Israeli Orthodox rabbinic thinkers in the post-war period.